Operasi Motor Induksi Tiga Fasa Pada Sistem Satu Fasa - Prabowo, Petrus Setyo; Christianto, Second Adrian (Media Teknika, 2017)
At this time the 3-phase induction motors are needed in many areas including  small industries and in areas  having  only 1-phase electrical system. The area requires a motor  with a large driving force that can be operated with both normal and 1-phase  electrical system. An induction motor can work  ineither  normal  configuration  or modified configuration with  adding a series  of  capacitor motors in 3-phase induction motor. The series capacitors are used  with an auxiliary coil is placed on the side or sides of the coil which has a larger impedance. In this study,  the performance of 3-phase induction motors  is supported  with 1-phase electrical system coupled with the ACS758 current sensor . This coupling is  to measure the current value of the load being used. When the ACS758 current sensor detects  the passing current, it will display  the current value on the LCD which  facilitates  the user in the current value of the measured reading. Induction motor can work well and normal with 1-phase electrical system using a series of capacitor motors. Measurement with current sensor has an error less than 2%.Keywords: 3-phase induction motor, 1-phase electrical system, LCD